Dear Son... - Stephen, Juanita (IYARIC, 2022)
Son is conversion about Black care - that which can be seen and that which cannot - and the emotional complexities of parenting in a context that, as Audre Lorde (1997) reminds us, we were never meant to survive (p.255).